A Zr-V-Cr-Si-C composite ceramic material containing a surface pre-oxidation layer and a preparation method thereof

By introducing inorganic fibers into the composite ceramic material and flame preoxidation treatment, a dense preoxidation layer is generated, which solves the problem of poor anti-oxidation protection effect of composite ceramic materials in high-temperature and high-speed airflow, and achieves better oxidation and ablation protection effect.

CN119219419BActive Publication Date: 2025-03-14CENT SOUTH UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411750512.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-03-14
Estimated Expiration
2044-12-02

AI Technical Summary

Technical Problem

Complex ceramic materials are prone to form holes and oxygen diffusion channels in high-temperature and high-speed airflow, resulting in poor anti-oxidation protection effect.

Method used

Inorganic fibers are introduced into the Zr-V-Cr-Si-C composite ceramic material, and a dense, continuous pre-oxidation layer is formed by flame pre-oxidation treatment, including the V2O5 phase, the Cr2O3 phase and the ZrO2 phase, which are filled in the ZrO2 skeleton to close pores and cracks.

Benefits of technology

An effective oxidation protection barrier is formed, which improves the material's anti-oxidation and ablation performance and enhances the protection of the inside of the matrix.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119219419B_ABST
    Figure CN119219419B_ABST
Patent Text Reader

Abstract

The present invention relates to a Zr-V-Cr-Si-C composite ceramic material containing a surface pre-oxidation layer and a preparation method thereof, and belongs to the field of composite material preparation. A phenolic resin solution is mixed with Zr powder, V powder, Cr powder, C powder and inorganic fiber and then pressed to obtain a blank I; after Si powder is laid on the surface of the blank I by an embedding method, silicon is infiltrated by a reactive melt infiltration method to obtain a blank II; the blank II is flame pre-oxidized to obtain a Zr-V-Cr-Si-C composite ceramic material containing a surface pre-oxidation layer, and the method can form a dense pre-oxidation layer on the surface of the composite ceramic material, which can act as an oxygen isolation barrier and effectively block oxygen from corroding the inside of the matrix.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a Zr-V-Cr-Si-C composite ceramic material containing a surface pre-oxidation layer and a preparation method thereof, belonging to the technical field of composite material preparation. Background Art

[0002] Composite ceramics are increasingly used in aerospace applications such as hypersonic vehicles. This material has good thermophysical properties, thermochemical properties, and anti-ablation properties.

[0003] However, after this composite material is oxidized and ablated by high-speed airflow, low-melting-point oxides such as SiO2 are easily volatile, which can easily lead to the formation of holes on the material surface, which develop into channels for oxygen diffusion and are not conducive to the antioxidant protection inside the matrix.

[0004] At the same time, under the action of high-speed airflow, the material on the surface of the composite ceramic is easily washed away, which is not conducive to the formation of a complete and stable oxidation protective layer of the material, and is extremely unfavorable to the protection of the interior of the material.

[0005] In order to improve the stability of multiphase materials in high-temperature and high-speed airflows and expand their application areas and scope, it is necessary to study the formation of a pre-oxidation protective barrier on the surface of the multiphase materials and explore a pre-oxidation process for multiphase materials that can form this protective pre-oxidation layer.

[0006] Through pre-oxidation process experiments, the researchers changed the material composition and distribution on the surface of the material and prepared a protective surface oxide layer to improve the antioxidant and corrosion resistance of the substrate.

[0007] A Chinese patent (publication number CN 118108510 A) discloses a method for preparing a composite ceramic material containing a surface oxide film, which is characterized in that: Zr powder, V powder, and C powder are mixed to obtain a mixed powder, the mixed powder is added to a phenolic resin solution, mixed, and then pressed to obtain a compact, the compact is embedded with silicon powder, and then reacted sintered and infiltrated with silicon to obtain a matrix carbide, and then the matrix carbide is pre-oxidized to obtain a composite ceramic material containing a surface oxide film. Although this method forms a dense oxide layer, its density, uniformity, flatness, and anti-oxidation and ablation protection still need to be strengthened. Summary of the invention

[0008] In view of the problems existing in the above-mentioned prior art, one of the objects of the present invention is to provide a method for preparing a Zr-V-Cr-Si-C composite ceramic material containing a surface pre-oxidation layer. The present invention adds Zr powder, V powder, Cr powder, C powder and inorganic fiber as raw materials to the Zr-V-Cr-Si-C composite ceramic, mixes the raw materials and then presses them into shape, siliconizes the formed body by melt infiltration, and then performs flame pre-oxidation treatment. This method can generate a continuous, dense and stable pre-oxidation layer on the surface of the composite ceramic material to form an oxidation protection barrier to protect the substrate. The preparation method is simple to operate, low in cost, short in cycle, good in controllability, and easy to realize mass production of products.

[0009] The second purpose of the present invention is to provide a Zr-V-Cr-Si-C composite ceramic material containing a surface pre-oxidation layer. After flame pre-oxidation treatment, a pre-oxidation layer is formed on the surface of the material. The pre-oxidation layer includes V2O5 phase, Cr2O3 phase, ZrO2 phase and SiO2 phase, and the V2O5 phase, Cr2O3 phase and SiO2 phase are filled in the ZrO2 skeleton, which can effectively close the pores, heal cracks well, etc., to form a dense, continuous, complete and hard vanadium-chromium-zirconium pre-oxidation layer, which can act as an oxidation protection barrier, effectively block the entry of oxygen, and produce a better oxidation protection effect on the inside of the matrix.

[0010] In order to achieve the above object, the present invention provides a method for preparing a Zr-V-Cr-Si-C composite ceramic material containing a surface pre-oxidation layer, the method comprising:

[0011] (1) mixing a phenolic resin solution with Zr powder, V powder, Cr powder, C powder and inorganic fiber and pressing the mixture to obtain a green body I;

[0012] (2) After laying Si powder on the surface of the blank I by an embedding method, silicon is infiltrated by a reactive infiltration method to obtain a blank II; the temperature of the reactive infiltration method is greater than the vacuum melting temperature of the inorganic fiber; the vacuum melting temperature of the inorganic fiber is less than 1700°C;

[0013] (3) The green body II is subjected to flame pre-oxidation treatment to obtain a Zr-V-Cr-Si-C composite ceramic material containing a surface pre-oxidation layer.

[0014] The innovation of the present invention lies in the introduction of inorganic fibers into the composite ceramic material. The introduction of inorganic fibers in the present invention mainly plays two roles. On the one hand, when the temperature is low during the reaction infiltration process, the inorganic fibers can play a wetting role in the matrix and promote the bonding reaction between different substances. On the other hand, when the temperature is high, the reaction of the inorganic fibers with the internal elements of the blank, the melting and volatilization of the inorganic fibers, etc. will promote the formation of through holes inside the Zr-V-Cr-Si-C material, forming a channel for molten silicon to penetrate into the matrix, promoting the penetration of molten silicon and filling the pores, which is beneficial to reduce the porosity of the Zr-V-Cr-Si-C sample after infiltration, making the infiltration sample more dense, and then the blank after infiltration is flame pre-oxidized. By controlling the process conditions of the flame pre-oxidation treatment, a Zr-V-Cr-Si-C composite material with a stable pre-oxidation layer on the surface can be prepared.

[0015] Flame pre-oxidation treatment generates a dense, continuous, complete and hard vanadium-chromium-zirconium pre-oxidation layer on the surface of the material through thermochemical reactions and thermophysical effects on the surface of the composite ceramic. This pre-oxidation layer acts as an oxidation protection barrier for the inside of the matrix, which can better resist the mechanical erosion of high-temperature, high-speed and high-oxygen gas flow, and is beneficial to enhancing the material's anti-oxidation and ablation performance. After the flame pre-oxidation process experiment, the ZrO2 skeleton structure is conducive to maintaining the structural stability of the pre-oxidation layer. The V2O5 phase and Cr2O3 phase can replace the evaporation and dissipation of SiO2 at high temperature, and can be filled in the ZrO2 skeleton, playing a good role in healing defects such as pores and cracks.

[0016] At the same time, Zr powder, V powder and Cr powder are introduced into the ceramic material of the present invention. The pre-oxidation layer formed after flame pre-oxidation treatment includes V2O5 phase, Cr2O3 phase and ZrO2 phase, and the V2O5 phase and Cr2O3 phase are filled in the ZrO2 skeleton, which can effectively close the pores. At the same time, this vanadium-chromium-zirconium pre-oxidation layer can act as an oxidation protection barrier, effectively blocking the entry of oxygen, and producing a good oxidation protection effect on the inside of the matrix. The vanadium atoms and oxygen atoms in the V2O5 layered crystal structure are connected by covalent bonds to form VO6 octahedrons. The three-dimensional network formed by these octahedrons makes the material have good stability and hardness; Cr2O3 has a high melting and boiling point, and the oxides of vanadium in different valence states will change with temperature. The combined effect of these reasons leads to the vanadium-chromium-zirconium pre-oxidation layer on the surface of the composite ceramic material being better retained on the surface of the material, thereby effectively protecting the matrix and forming an effective oxidation ablation protection barrier for the inside of the matrix.

[0017] In a preferred embodiment, the length of the inorganic fiber is 1 to 6 mm.

[0018] In a preferred embodiment, the inorganic fiber is selected from at least one of titanium fiber, glass fiber, aluminum fiber and steel fiber.

[0019] The inventors found that under long-term heat preservation during the infiltration process, the inorganic fibers react with the elements inside the blank, melt and volatilize, etc., leaving gaps inside the material, forming channels for molten silicon to penetrate into the matrix.

[0020] According to a particularly preferred specific embodiment, when the inorganic fiber is aluminum fiber, the method also includes first grinding the aluminum fiber with sandpaper, and then mixing the grinded aluminum fiber with Zr powder, V powder, Cr powder, and C powder. The grinding is mainly to remove the aluminum oxide film on the surface of the aluminum fiber to facilitate the smooth progress of the experimental process.

[0021] In a preferred embodiment, the mass ratio of Zr powder: V powder: Cr powder: C powder is 0.5~2:2~3:2~3:1.

[0022] More preferably, the mass ratio of Zr powder:V powder:Cr powder:C powder is 0.5~1.5:2~2.5:2~2.5:1.

[0023] The inventors found that by controlling the composition ratio of Zr powder, V powder, Cr powder and C powder within the above range, a denser vanadium-chromium carbide phase can be formed. In addition, the high-temperature performance of the carbide is relatively good. After the pre-oxidation process, the composite material is transformed into a composite material with a surface pre-oxidation layer. This composite material has better oxidation and ablation protection. If the proportion of Zr powder is too high, there will be too much ZrO2 skeleton formed by oxidation of ZrC, and too little carbide phase generated by V powder and Cr powder, which will easily lead to the continuous vanadium-chromium oxide layer generated by pre-oxidation on the surface of the material not being dense enough, and unable to fill the pores well, which is not conducive to the stability of the internal structure of the material.

[0024] In a preferred embodiment, the C powder is carbon powder and / or graphite powder.

[0025] It should be noted that the present invention has no special requirements on the particle sizes of Zr powder, V powder, Cr powder, C powder and Si powder, and any particle sizes known in the art may be used.

[0026] In a preferred embodiment, the amount of the inorganic fiber is 1 wt% to 5 wt% based on the total weight of the Zr powder, V powder, Cr powder, C powder and inorganic fiber. Too much inorganic fiber may cause cracking of the green body, while too little inorganic fiber may not achieve the densification effect.

[0027] Further preferably, the amount of the inorganic fiber is 1 wt% to 3 wt%.

[0028] In a preferred embodiment, based on the total mass of the Zr powder, the V powder, the Cr powder, the C powder and the inorganic fiber, the amount of the phenolic resin solution is 10 wt % to 20 wt %.

[0029] In a preferred embodiment, the phenolic resin solution is a combination of phenolic resin and anhydrous ethanol in a mass ratio of 1:2-4.

[0030] In a preferred embodiment, the green body I is dried before the siliconizing.

[0031] In a preferred embodiment, based on the total amount of the green body I and the Si powder, the amount of the Si powder is 30-40wt%.

[0032] It should be noted that the present invention has no special requirements for the drying conditions, and any conditions known in the art may be used.

[0033] In a preferred embodiment, the reaction infiltration method is carried out under vacuum conditions at a temperature of 1700-1800° C. for 2-5 hours.

[0034] Further preferably, the conditions of the reactive infiltration method are: keeping the temperature at 1700-1750° C. for 2-3 hours.

[0035] In a preferred embodiment, the operating steps of the reactive infiltration method include: firstly laying Si powder by embedding method, laying 20-35wt% of Si powder under the compact, then laying 65-80wt% of Si powder above the compact, and then performing reactive infiltration method for siliconization.

[0036] In a preferred embodiment, the porosity of the green body II is 4% to 30%.

[0037] In a preferred embodiment, the flame pre-oxidation treatment adopts oxyacetylene flame oxidation, the oxyacetylene flame is an oxidizing flame, the oxyacetylene contains oxygen and acetylene, and the flow ratio of oxygen to acetylene is 1:0.75~0.84, the flame temperature is 1800℃~2500℃, the vertical distance between the ablated surface of the blank II and the flame nozzle is ≥20mm, and the pre-oxidation treatment time is 5s~30s.

[0038] Further preferably, the flame temperature is 1800°C to 2300°C, the vertical distance between the ablated surface of the blank II and the flame nozzle is ≥25mm, and the pre-oxidation treatment time is 5s to 10s. In the present invention, the flame pre-oxidation treatment conditions are controlled within the above range, which can effectively generate a stable pre-oxidation layer on the surface of the Zr-V-Cr-Si-C composite material, avoid the occurrence of warping and other phenomena, and can better reduce the mechanical erosion of the substrate surface phase by the high-speed airflow. Under this preferred condition, the surface pre-oxidation layer of the generated composite material has the characteristics of stability and density, which can produce a good oxidation protection effect on the composite material matrix and improve the material's anti-oxidation and ablation performance.

[0039] In a preferred embodiment, the flow rate of oxygen is 700-1200 L / h.

[0040] Further preferably, the flow rate of the oxygen is 800-1100 L / h.

[0041] The present invention also provides a Zr-V-Cr-Si-C composite ceramic material containing a surface pre-oxidation layer prepared by the above-mentioned preparation method. The composite ceramic material is composed of a matrix carbide layer and a surface pre-oxidation layer, the matrix carbide layer contains a ZrC phase, a VC phase, a V2C phase, a SiC phase, etc., the pre-oxidation layer includes a V2O5 phase, a Cr2O3 phase and a ZrO2 phase, and the V2O5 phase and the Cr2O3 phase are filled in the ZrO2 skeleton, which can effectively close the pores, and the pre-oxidation layer can form an effective oxidation and ablation protection barrier for the inside of the matrix.

[0042] Compared with the prior art, the present invention has at least the following advantages:

[0043] (1) The purpose of introducing inorganic fibers into composite ceramic materials by traditional methods is mainly to improve their mechanical properties. However, the present invention improves the anti-oxidation and ablation protection of the surface of composite ceramic materials by adding inorganic fibers. The chopped inorganic fibers used in the present invention can not only wet the internal substances of the material and promote the combination of substances, but also effectively form pores and provide channels for the infiltration of molten silicon, thereby enhancing the reaction of the internal substances of the material, reducing the porosity of the infiltration sample, and facilitating the subsequent pre-oxidation process operation.

[0044] (2) In the preparation method of the present invention, the reactive infiltration method adopted by the present invention for silicon infiltration has low cost, short preparation time, easy operation, and good dimensional stability of the blank; and the oxyacetylene flame pre-oxidation process adopted by the present invention has a short production cycle, convenient experimental operation, high production efficiency, good flame controllability, low economic cost, and is easy to realize industrial production of the product.

[0045] (3) A dense pre-oxidation layer is formed on the surface of the composite ceramic material prepared by the method of the present invention, which can act as an oxygen isolation barrier and effectively block the erosion of oxygen to the inside of the matrix. This pre-oxidation layer structure is of great significance for improving the stability of the material and its adaptability to harsh environments. Moreover, the surface pre-oxidation layer is complete, hard and dense, which can effectively improve the material's anti-oxidation and ablation performance.

[0046] (4) The preparation method is simple to operate, low in cost, short in cycle, good in controllability, and easy to realize mass production of products. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Figure 1 Schematic diagram of the structure of Zr-V-Cr-Si-C composite ceramic material after flame pre-oxidation treatment; wherein, 1-surface pre-oxidation layer, 2-matrix.

[0048] Figure 2 This is a physical picture of the sample of the composite ceramic material prepared in Example 1;

[0049] Figure 3 This is the SEM-EDS image of the green body obtained after reactive infiltration in Example 1; wherein, Figure 3 (a) is the microscopic morphology. Figure 3 (b) is the backscattered electron image of the cross section of the blank;

[0050] Figure 4 The XRD pattern of the pre-oxidation layer surface of the composite ceramic material prepared in Example 1;

[0051] Figure 5 This is an EDS surface scan of the surface of the composite ceramic material sample prepared in Example 1; wherein, Figure 5 (a) is the microscopic morphology of the pre-oxidation layer. Figure 5 (b) is the microscopic distribution diagram of Zr. Figure 5 (c) in the figure is the microscopic distribution diagram of V. Figure 5 (d) in the figure is the microscopic distribution diagram of Cr. Figure 5 (e) in the figure is the microscopic distribution diagram of Si. Figure 5 (f) in the figure is the microscopic distribution diagram of C. Figure 5 (g) shows the microscopic distribution of O;

[0052] Figure 6 This is a cross-sectional BSE image of the pre-oxidized layer of the composite ceramic material prepared in Example 1;

[0053] Figure 7 The surface XRD pattern of the pre-oxidation layer of the composite ceramic material prepared in Example 2;

[0054] Figure 8 This is a surface SEM image of the pre-oxidation layer of the composite ceramic material prepared in Example 2;

[0055] Fig. 9 This is a cross-sectional SEM image of the pre-oxidation layer of the composite ceramic material prepared in Example 2. DETAILED DESCRIPTION

[0056] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0057] In the present invention, normal temperature refers to 25±2°C.

[0058] The present invention is further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited to the following specific embodiments. Obviously, the embodiments described below are only a part of the embodiments, and all other embodiments obtained by professionals in this field without creative work still belong to the protection scope of the present invention.

[0059] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0060] The amount of C powder used in the following examples is 3g.

[0061] Example 1

[0062] Raw material information:

[0063] Select Zr powder (particle size 300 mesh), V powder (particle size 325 mesh, purity 99.9%), Cr powder (particle size 300 mesh, purity 99.9%), C powder (graphite powder, particle size 325 mesh, purity 99.9%) and Si powder (particle size 5 microns, purity 99.9%) and chopped glass fiber (1~3mm) as raw materials, weigh the powders according to the proportion, and the mass ratio is: Zr powder: V powder: Cr powder: C powder = 1:2.2:2.2:1; based on the total mass of Zr powder, V powder, Cr powder, C powder and chopped glass fiber, the amount of chopped glass fiber is 1wt%, and the amount of phenolic resin alcohol solution is 15wt%.

[0064] (1) Zr powder, V powder, Cr powder, C powder and chopped glass fiber are mixed evenly, and phenolic resin alcohol solution (the ratio of phenolic resin to anhydrous ethanol is 1:3 by mass ratio) is added to the mixture and mixed evenly, and the mixed powder is placed in a powder tablet press and pressed at room temperature to obtain a green body I, which is then dried in an oven (temperature 40°C, time 12 h);

[0065] (2) The dried green body I was paved with Si powder by the embedding method (based on the total amount of green body I and Si powder, the amount of Si powder was 35wt%). The mass ratio of Si powder at the top and bottom of the sample was 7:3. Then, a reactive infiltration experiment was carried out to infiltrate silicon powder into the green body. The sintering was carried out in a vacuum, and the temperature was raised to 1750°C and kept at this temperature for 3h to obtain green body II.

[0066] (3) Flame pre-oxidation treatment was carried out using oxyacetylene flame oxidation. The body II was fixed on the sample stage. The vertical distance between the oxidized surface of the sample and the flame nozzle was 30 mm. The oxygen flow rate of the oxyacetylene gas was maintained at 1040 L / h, the acetylene flow rate was 800 L / h, the flame pre-oxidation temperature was 2000-2300 °C, and the flame pre-oxidation time was 10 s. A Zr-V-Cr-Si-C composite ceramic material containing a surface pre-oxidation layer was obtained. The pre-oxidation layer was well bonded to the substrate, had a hard texture, and had a complete and dense surface morphology.

[0067] Figure 3 This is the SEM-EDS image of the green body obtained after reactive infiltration in Example 1; wherein, Figure 3 (a) is the microscopic morphology. Figure 3 (b) is the backscattered electron image of the cross section of the green body; it can be seen from the figure that the composite ceramic phases after reactive infiltration are closely bonded, the porosity level is not high, the porosity is 9.42%, and no chopped glass fibers are seen, indicating that the fibers melt and volatilize during the heating process, which is conducive to the flame pre-oxidation treatment.

[0068] Figure 4 This is the XRD pattern of the pre-oxidation layer surface of the composite ceramic material prepared in Example 1; it can be concluded from the figure that the contents of V2O5 and Cr2O3 phases are both high, indicating that the pre-oxidation layer on the surface of the sample is mainly composed of a ZrO2 skeleton and V2O5 and Cr2O3 phases.

[0069] Figure 5 This is an EDS surface scan of the surface of the composite ceramic material sample prepared in Example 1; wherein, Figure 5 (a) is the microscopic morphology of the pre-oxidation layer. Figure 5 (b) is the microscopic distribution diagram of Zr. Figure 5 (c) in the figure is the microscopic distribution diagram of V. Figure 5 (d) in the figure is the microscopic distribution diagram of Cr. Figure 5 (e) in the figure is the microscopic distribution diagram of Si. Figure 5 (f) in the figure is the microscopic distribution diagram of C. Figure 5 (g) is the microscopic distribution diagram of O; it can be seen from the figure that the vanadium-chromium oxidation products in the surface pre-oxidation layer are integrated to form a vanadium-chromium oxide layer, and combined with the effect of zirconium oxide, a vanadium-chromium-zirconium pre-oxidation layer is formed.

[0070] Figure 6 This is a cross-sectional BSE diagram of the pre-oxidation layer of the composite ceramic material prepared in Example 1; the section between the upper and lower dotted lines in the figure is a cross-sectional diagram of the pre-oxidation layer. It can be seen from the figure that the cross-sectional morphology of the pre-oxidation layer is relatively dense.

[0071] The Zr-V-Cr-Si-C composite ceramic material obtained in this example was subjected to an oxyacetylene flame ablation experiment. The ablation experiment was carried out in accordance with the national military standard GJB323A-96. The oxyacetylene flame flow was used as the heat source and the flame flow was directed at the sample surface at an angle of 90 degrees. The material was ablated and washed for 10 seconds at an ablation temperature of about 2200°C. The mass ablation rate of the composite material after ablation was about 1.86 mg / s, indicating that the surface pre-oxidation layer of the Zr-V-Cr-Si-C composite material was relatively dense and could serve as an oxygen ablation barrier; and after ablation, the surface pre-oxidation layer of the composite material was intact in morphology, indicating that the composite material had good anti-oxidation and ablation properties.

[0072] Example 2

[0073] Zr powder (particle size 300 mesh), V powder (particle size 325 mesh, purity 99.9%), Cr powder (particle size 300 mesh, purity 99.9%), C powder (graphite powder, particle size 325 mesh, purity 99.9%), Si powder (particle size 5 microns, purity 99.9%) and chopped aluminum fibers (1-3 mm) were selected as raw materials, and the powders were weighed according to the proportion, and the mass ratio was: Zr powder: V powder: Cr powder: C powder = 0.9:2.5:2.5:1; based on the total mass of Zr powder, V powder, Cr powder, C powder and chopped aluminum fibers, the amount of chopped aluminum fibers was 2wt%, and the amount of phenolic resin alcohol solution was 12wt%.

[0074] (1) First, the chopped aluminum fiber is polished with sandpaper, and then Zr powder, V powder, Cr powder, C powder and chopped aluminum fiber are mixed evenly, and phenolic resin alcohol solution (the ratio of phenolic resin to anhydrous ethanol is 1:3 by mass ratio) is added to the mixture and mixed evenly, and the mixed powder is placed in a powder tablet press and pressed at room temperature to obtain a blank I, which is then dried in an oven (temperature of 40°C for 12 h);

[0075] (2) The dried green body I was paved with Si powder by embedding method (based on the total amount of green body I and Si powder, the amount of Si powder was 30wt%). The mass ratio of Si powder at the top and bottom of the sample was 2:8. Then, a reactive infiltration experiment was carried out to infiltrate silicon powder into the green body. The sintering was carried out in vacuum, and the temperature was raised to 1700℃ and kept at this temperature for 4h to obtain green body II.

[0076] (3) Flame pre-oxidation treatment was carried out using oxyacetylene flame oxidation. The body II was fixed on the sample stage. The vertical distance between the oxidized surface of the sample and the flame nozzle was 30 mm. The oxygen flow rate of the oxyacetylene gas was maintained at 1040 L / h, the acetylene flow rate was 800 L / h, the flame pre-oxidation temperature was 2000-2300 °C, and the flame pre-oxidation time was 10 s. A Zr-V-Cr-Si-C composite ceramic material containing a surface pre-oxidation layer was obtained. The pre-oxidation layer was well bonded to the substrate and was relatively complete, dense, and hard in macroscopic terms.

[0077] Figure 7 This is the surface XRD pattern of the pre-oxidation layer of the composite ceramic material prepared in Example 2; it can be seen from the figure that the pre-oxidation layer on the surface of the composite material is mainly composed of V2O5 phase, Cr2O3 phase and ZrO2 phase.

[0078] Figure 8 This is a surface SEM image of the pre-oxidation layer of the composite ceramic material prepared in Example 2; it can be seen from the image that the pre-oxidation layer is relatively uniformly and evenly distributed on the surface of the substrate.

[0079] Fig. 9 This is a cross-sectional SEM image of the pre-oxidation layer of the composite ceramic material prepared in Example 2; the cross-sectional image of the pre-oxidation layer is between the upper and lower dotted lines in the figure. It can be seen that the cross-sectional image of the pre-oxidation layer shows relatively few pores, and the porosity is 8.65%.

[0080] The Zr-V-Cr-Si-C composite ceramic material obtained in this example was subjected to an oxyacetylene flame ablation test. The oxyacetylene flame ablation test was carried out in accordance with the national military standard GJB323A-96. The oxyacetylene flame flow was used as the heat source and the flame flow was directed at the sample surface at an angle of 90 degrees. The material was ablated and flushed for 10 seconds at an ablation temperature of about 2200°C. The mass ablation rate of the composite material after ablation was about 1.73 mg / s. This shows that the surface pre-oxidation layer of the Zr-V-Cr-Si-C composite material is relatively dense and can act as an oxygen ablation barrier; and the surface pre-oxidation layer of the composite material is intact after ablation, indicating that the composite material has good anti-oxidation and ablation properties.

[0081] Comparative Example 1

[0082] Step (1) and step (2) are the same as in Example 1, to obtain body II;

[0083] Omit step (3).

[0084] The obtained blank II without the surface pre-oxidation layer was subjected to an oxyacetylene flame ablation test, and the ablation test was carried out in accordance with the national military standard GJB323A-96. The oxyacetylene flame flow was used as the heat source and the flame flow was directed at the sample surface at an angle of 90 degrees. The material was ablated and washed for 10 seconds at an ablation temperature of about 2200°C. The mass ablation rate of the composite material after ablation was about 5.59 mg / s.

[0085] Comparative Example 2

[0086] Step (1) and step (2) are the same as in Example 2 to obtain body II;

[0087] Omit step (3).

[0088] The obtained blank II without the surface pre-oxidation layer was subjected to an oxyacetylene flame ablation test, and the ablation test was carried out in accordance with the national military standard GJB323A-96. The oxyacetylene flame flow was used as the heat source and the flame flow was directed at a 90-degree angle to the sample surface, and the material was ablated and washed for 10 seconds at an ablation temperature of about 2200°C. The mass ablation rate of the composite material after ablation was about 5.85 mg / s.

[0089] Comparative Example 3

[0090] This comparative example was carried out in a similar manner to Example 1, except that no Cr powder was added in step (1) of this comparative example, and steps (2) and (3) were the same as in Example 1.

[0091] The Zr-V-Cr-Si-C composite ceramic material obtained in this comparative example was subjected to an oxyacetylene flame ablation test, and the ablation test was conducted in accordance with the national military standard GJB323A-96. The oxyacetylene flame flow was used as a heat source and the flame flow was directed at a 90-degree angle to the sample surface, and the material was ablated and washed for 10 seconds at an ablation temperature of about 2200°C. The mass ablation rate of the composite material after ablation was about 3.26 mg / s.

[0092] Comparative Example 4

[0093] This comparative example was carried out in a similar manner to Example 1, except that in step (1) of this comparative example, chopped glass fibers were not added, and steps (2) and (3) were the same as in Example 1.

[0094] The Zr-V-Cr-Si-C composite ceramic material obtained in this comparative example was subjected to an oxyacetylene flame ablation test, and the ablation test was conducted in accordance with the national military standard GJB323A-96. The oxyacetylene flame flow was used as a heat source and the flame flow was directed at a 90-degree angle to the sample surface, and the material was ablated and washed for 10 seconds at an ablation temperature of about 2200°C. The mass ablation rate of the composite material after ablation was about 3.79 mg / s.

[0095] The above results show that the Zr-V-Cr-Si-C composite ceramic material containing a surface pre-oxidation layer prepared by the method provided by the present invention can effectively close the pores, and the surface pre-oxidation layer can better serve as an oxygen ablation barrier to protect the interior of the matrix from further oxidation and ablation. At the same time, the pre-oxidation layer is well bonded to the matrix, dense, and hard, which helps to improve the overall anti-oxidation and ablation performance of the material.

[0096] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A method for preparing a Zr-V-Cr-Si-C composite ceramic material containing a surface pre-oxidation layer, characterized in that: The following steps are involved: (1) A phenolic resin solution is mixed with Zr powder, V powder, Cr powder, C powder and inorganic fiber and then pressed to obtain a green body I; in terms of mass ratio, Zr powder: V powder: Cr powder: C powder = 0.5~2:2~3:2~3:1; (2) After laying Si powder on the surface of the blank I by an embedding method, silicon is infiltrated by a reactive infiltration method to obtain a blank II; the temperature of the reactive infiltration method is greater than the vacuum melting temperature of the inorganic fiber; the vacuum melting temperature of the inorganic fiber is less than 1700°C; (3) The green body II is subjected to flame pre-oxidation treatment to obtain a Zr-V-Cr-Si-C composite ceramic material containing a surface pre-oxidation layer.

2. The method for preparing a Zr-V-Cr-Si-C composite ceramic material containing a surface pre-oxidation layer according to claim 1, characterized in that: The length of the inorganic fiber is 1-6 mm.

3. The method for preparing a Zr-V-Cr-Si-C composite ceramic material containing a surface pre-oxidation layer according to claim 2, characterized in that: The inorganic fiber is selected from at least one of titanium fiber, glass fiber, aluminum fiber and steel fiber.

4. The method for preparing a Zr-V-Cr-Si-C composite ceramic material containing a surface pre-oxidation layer according to any one of claims 1 to 3, characterized in that: Based on the total weight of Zr powder, V powder, Cr powder, C powder and inorganic fiber, the amount of the inorganic fiber is 1wt% to 5wt%.

5. The method for preparing a Zr-V-Cr-Si-C composite ceramic material containing a surface pre-oxidation layer according to any one of claims 1 to 3, characterized in that: The conditions of the reaction infiltration method are: under vacuum conditions, at a temperature of 1700-1800° C., and keeping warm for 2-5 hours.

6. The method for preparing a Zr-V-Cr-Si-C composite ceramic material containing a surface pre-oxidation layer according to any one of claims 1 to 3, characterized in that: The porosity of the green body II is 4% to 30%.

7. The method for preparing a Zr-V-Cr-Si-C composite ceramic material containing a surface pre-oxidation layer according to any one of claims 1 to 3, characterized in that: The flame pre-oxidation treatment adopts oxyacetylene flame oxidation, the oxyacetylene flame is an oxidizing flame, the oxyacetylene contains oxygen and acetylene, and the flow ratio of oxygen to acetylene is 1:0.75~0.84, the flame temperature is 1800°C~2500°C, the vertical distance between the ablated surface of the blank II and the flame nozzle is ≥20mm, and the pre-oxidation treatment time is 5s~30s.

8. The method for preparing a Zr-V-Cr-Si-C composite ceramic material containing a surface pre-oxidation layer according to claim 7, characterized in that: The flow rate of the oxygen is 700-1200 L / h.

9. A Zr-V-Cr-Si-C composite ceramic material containing a surface pre-oxidation layer obtained by the preparation method according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Multiphase ceramic material containing surface oxidation film and preparation method of multiphase ceramic material

    CN118108510A

  • CC-ZrC-Cr3C2 composite material prepared by reactive melt infiltration method

    CN111777425A

  • Method for preparing multi-element ultrahigh-temperature ceramic coating through coating-reactive infiltration

    CN114276142A